High-performance partially aligned semiconductive single-walled carbon nanotube transistors achieved with a parallel technique - Wang, Yilei (2014)
Single-walled carbon nanotubes (SWNTs) are widely thought to be a strong contender for next-generation printed electronic transistor materials. However, large-scale solution-based parallel assembly of SWNTs to obtain high-performance transistor devices is challenging. SWNTs have anisotropic properties and, although partial alignment of the nanotubes has been theoretically predicted to achieve optimum transistor device performance, thus far no parallel solution-based technique can achieve this. Herein a novel solution-based technique, the immersion-cum-shake method, is reported to achieve partially aligned SWNT networks using semiconductive (99% enriched) SWNTs (s-SWNTs). By immersing an aminosilane-treated wafer into a solution of nanotubes placed on a rotary shaker, the repetitive flow of the nanotube solution over the wafer surface during the deposition process orients the nanotubes toward the fluid flow direction. By adjusting the nanotube concentration in the solution, the nanotube density of the partially aligned network can be controlled; linear densities ranging from 5 to 45 SWNTs/μm are observed. Through control of the linear SWNT density and channel length, the optimum SWNT-based field-effect transistor devices achieve outstanding performance metrics (with an on/off ratio of ~3.2 × 104 and mobility 46.5 cm2/Vs). Atomic force microscopy shows that the partial alignment is uniform over an area of 20 × 20 mm2 and confirms that the orientation of the nanotubes is mostly along the fluid flow direction, with a narrow orientation scatter characterized by a full width at half maximum (FWHM) of <15° for all but the densest film, which is 35°. This parallel process is large-scale applicable and exploits the anisotropic properties of the SWNTs, presenting a viable path forward for industrial adoption of SWNTs in printed, flexible, and large-area electronics.